Analisis Dampak Kombinasi Bisnis Melalui Akuisisi Terhadap Kinerja Keuangan Perusahaan Pada Sektor Finance Non Perbankan - Yosep Eka Putra; Mega Rahmi; Sari Ramadani Fitri; Rahmi Rahmadani; Riza Yulia Putri; Rena Karmila (INDO PUBLISHING, 2026)
This study analyzes the impact of acquisitions on the financial performance of non-banking financial companies listed on the Indonesia Stock Exchange during 2023–2025. A quantitative descriptive and causal design was used with a sample of 30 companies selected through purposive sampling. Financial performance is measured using ROA, ROE, DER, and NPM. Since the data are not normally distributed (p < 0.05), non-parametric tests (Friedman and Kruskal-Wallis) were applied. Descriptive results show high variability in performance indicators across firms. The results indicate no significant differences in ROA, ROE, DER, and NPM before and after acquisitions (p > 0.05), suggesting that acquisition synergies have not yet materialized in the short term and may require a longer period to have a measurable effect.